Characteristics of Virgin and Recycled Asphalt Shingle Binder Blends: Rheological and Chemical Properties. Issue 1 (January 2014) - Zhou, Fujie; Chen, Peiru; Huang, Shin-Che
Application of recycled asphalt shingles (RAS) into hot-mix asphalt have been well accepted by many transportation agencies in recent years. However, limited information on virgin-RAS binder blends is available. This study focused on the rheological and chemical characteristics of different blends. Two virgin binders (PG 64-22A and PG 64-22B) and three RAS binders (original RAS binder, extracted RAS binders from tear-off, and manufacture waste asphalt shingles) were used. Different from the well-known linear blending of virgin and reclaimed asphalt pavement binders, the virgin and RAS binder blending followed a nonlinear trend. The nonlinear behavior was found to relate closely to the asphaltene content of the virgin and RAS blends. Furthermore, the identified nonlinear behavior could be described by a simple linear equation because the normalized increase in high-temperature performance grade varied linearly with the increase in the RAS binder content. The Christensen–Anderson (CA) model and the Williams–Landel–Ferry (WLF) shifting equation successfully described the complex shear modulus behavior of different blends of virgin and RAS binders. The results also showed that adding RAS binders to virgin binders had a similar impact as that of aging on rheological parameters such as the rheological index, crossover frequency, and WLF parameters. The addition of RAS binder reduced the temperature susceptibility of virgin binders. In addition, the study found that the carbonyl area measured with a Fourier transform infrared-attenuated total reflectance spectroscopy was highly related to the CA model and the WLF shifting parameters.